Diatoms for Carbon Sequestration and Bio-Based Manufacturing - Sethi, Deepak (Biology (Basel), 2020)
Carbon dioxide (CO(2)) is a major greenhouse gas responsible for climate change. Diatoms, a natural sink of atmospheric CO(2), can be cultivated industrially in autotrophic and mixotrophic modes for the purpose of CO(2) sequestration. In addition, the metabolic diversity exhibited by this group of photosynthetic organisms provides avenues to redirect the captured carbon into products of value. These include lipids, omega-3 fatty acids, pigments, antioxidants, exopolysaccharides, sulphated polysaccharides, and other valuable metabolites that can be produced in environmentally sustainable bio-manufacturing processes. To realize the potential of diatoms, expansion of our knowledge of carbon supply, CO(2) uptake and fixation by these organisms, in conjunction with ways to enhance metabolic routing of the fixed carbon to products of value is required. In this review, current knowledge is explored, with an evaluation of the potential of diatoms for carbon capture and bio-based manufacturing.